Punishment in Disguise : Penal Governance and Canadian Women's Imprisonment. (University of Toronto Press, 2001)
In "Punishment in Disguise", Kelly Hannah-Moffat presents a look at some current forms of penal governance in Canadian federal women's prisons. Hannah-Moffat uses women's imprisonment to theorize the complexity of penal power and to show how the meaning and content of women's penal governance changes over time, how penal reform strategies intersect and evolve into complex patterns of governing, how governing is always gendered and racialized, and how expert, non-expert, and hybrid forms of power and knowledge inform penal strategies. The author posits that although there has been a series of distinct phases in the imprisonment of women, the prison system itself, given its primary functions of custody and punishment, is consistent in thwarting attempts at progressive reform. While each distinct phase has its own corresponding ideology and discourse, the individual discourses have internal complexities and contradictions, which have not been adequately recognized in the general literature on penology. Avoiding universal and reductionist claims about women's oppression, Hannah-Moffat argues that relations of power are complex and fractured and that there is a need to explore the specific elements of institutional power relations. Backed by solid research, "Punishment in Disguise" makes a strong contribution to criminology and feminist theory by providing an alternative approach to analysing the governance of women by other women and by the state.